Isolation and escape mapping of broadly neutralizing antibodies against emerging delta-coronaviruses - Rexhepaj, Megi; Asarnow, Daniel; Perruzza, Lisa; Park, Young-Jun; Guarino, Barbara; Mccallum, Mathew; Culap, Katja; Saliba, Christian; Leoni, Giada; Balmelli, Alessio; Yoshiyama, Courtney N.; Dickinson, Miles S.; et al. (Immunity (Cambridge, Mass.), 2024)
Porcine delta-coronavirus (PDCoV) spillovers were recently detected in febrile children, underscoring the recurrent zoonoses of divergent CoVs. To date, no vaccines or specific therapeutics are approved for use in humans against PDCoV. To prepare for possible future PDCoV epidemics, we isolated PDCoV spike (S)-directed monoclonal antibodies (mAbs) from humanized mice and found that two, designated PD33 and PD41, broadly neutralized a panel of PDCoV variants. Cryoelectron microscopy (cryo-EM) structures of PD33 and PD41 in complex with the S receptor-binding domain (RBD) and ectodomain trimer revealed the epitopes recognized by these mAbs, rationalizing their broad inhibitory activity. We show that both mAbs competitively interfere with host aminopeptidase N binding to neutralize PDCoV and used deep-mutational scanning epitope mapping to associate RBD antigenic sites with mAb-mediated neutralization potency. Our results indicate a PD33-PD41 mAb cocktail may heighten the barrier to escape. PD33 and PD41 are candidates for clinical advancement against future PDCoV outbreaks. [Display omitted] •Isolation of PDCoV RBD-directed human neutralizing mAbs•Molecular basis of mAb-mediated broad PDCoV neutralization revealed by cryo-EM•Potent PDCoV neutralization involves competitive inhibition of receptor engagement•Deep-mutational scanning identification of a mAb cocktail to limit viral resistance Porcine delta-coronavirus (PDCoV) recently spilled over to humans, and no countermeasures are approved. Rexhepaj et al. describe human mAbs that broadly neutralize PDCoV variants by inhibiting host receptor engagement to the RBD. They perform deep-mutational scanning to enhance our understanding of DCoV immunity and identify a two-mAb cocktail that could potentially limit viral resistance.